Simultaneous robot-assisted radical cystoprostatectomy and nephroureterectomy in a patient with multifocal invasive urothelial carcinoma and previous contralateral nephroureterectomy - (:unkn) unknown (My University, 2013)
We present a case of simultaneous robot-assisted radical cystoprostatectomy and nephroureterectomy with extended lymphadenectomy for multifocal invasive urothelial carcinoma in a patient with recurrent high-grade urothelial cancer and a previous right nephroureterectomy. The total urinary exenteration and extended lymphadenectomy was successfully performed with robot-assisted surgery in this unique case where the patient was rendered anephric at the end of the operation. We discuss the operative steps and the techniques performed to optimize the oncological results of robot-assisted surgery for invasive urothelial carcinoma, while attempting to preserve the renal function until the patient's urinary system was totally exenterated. © 2012 Springer-Verlag London Ltd.
Keywords: Bladder cancer; Kidney cancer; Robotic surgery; Total urinary exenteration; Urothelial carcinoma